Fast Acoustic Wave Sparsely Activated Localization Microscopy (fast-AWSALM) Ultrasound Super-Resolution using Plane-Wave Activation of Nanodroplets - Zhang, Ge (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2019)
Localization-based ultrasound super-resolution imaging using microbubble contrast agents and phase-change nano-droplets has been developed to visualize microvascular structures beyond the diffraction limit. However, the long data acquisition time makes the clinical translation more challenging. In this study, fast acoustic wave sparsely activated localization microscopy (fast-AWSALM) was developed to achieve super-resolved frames with sub-second temporal resolution, by using low-boiling-point octafluoropropane nanodroplets and high frame rate plane waves for activation, destruction, as well as imaging. Fast-AWSALM was demonstrated on an in vitro microvascular phantom to super-resolve structures that could not be resolved by conventional B-mode imaging. The effects of the temperature and mechanical index on fast-AWSALM was investigated. Experimental results show that sub-wavelength micro-structures as small as 190 lm were resolvable in 200 ms with plane-wave transmission at a center frequency of 3.5 MHz and a pulse repetition frequency of 5000 Hz. This is about a 3.5 fold reduction in point spread function full-width-half-maximum compared to that measured in conventional B-mode, and two orders of magnitude faster than the recently reported AWSALM under a non-flow/very slow flow situations and other localization based methods. Just as in AWSALM, fast-AWSALM does not require flow, as is required by current microbubble based ultrasound super resolution techniques. In conclusion, this study shows the promise of fast-AWSALM, a super-resolution ultrasound technique using nanodroplets, which can generate super-resolution images in milli-seconds and does not require flow